Lipid regulation of exocytosis - Zhang, Jing (2010)
Exocytosis is a finely tuned program in which the secretory vesicles are directed to fuse with plasma membrane and discharge neurotransmitter or hormone content to the extracellular space. Lipids may modulate exocytosis via interplays with exocytotic proteins, or via their influence on the physicochemical and structural properties of the plasma membrane. In the current work, we explored the multiple roles played by lipids in the regulation of exocytosis. We mainly focused on (1) sterols and sphingolipids which are enriched in membrane functional microdomains (lipid rafts) for spatial regulation of exocytosis; and (2) lysophospholipids which are implicated in Ca2+ signaling. It was found that lipids regulate multiple aspects of exocytosis, such as vesicle trafficking, docking and quantal release kinetics. Understanding the regulatory roles of lipids in the dynamic exocytotic cascade would assist to fully reveal this fundamental cell function and to deal with diseases related to exocytosis.